The 2030 Agenda: trends of transition toward sustainability - Guerra, João (2018)
Sustainability is a ubiquitous landmark in contemporaneity, and its definition is as diverse as it is ambiguous. On its behalf, the Earth and Mankind’s salvation is often claimed, but more than the planet’s rescue, what sustainability implies is the reinforcement of the transition process through new social practices and behaviours (Veiga 2011 [2010]). It is an outcry for innovative ways of preserving the commons, and to efficiently maintain the ecosystems’ biocapacity on which depends the conditions of existence of the present and the future generations.